Max-min fuzzy programming approach for compromise farming: a case study - Mousumi Kumar; Sankhajit Roy (Agricultural Economics Research Review, 2023)
Applying max-min fuzzy programming approach this paper shows how farmers can maximize income through re-allocation of land and other productive resources. In this approach, utilization of total cultivable land, achievement of the aspiration levels of production of seasonal crops and achievement of overall profit throughout the planning year, are fuzzily described. In model formulation and solution process the max-min fuzzy programming is used to qualify the ‘compromise solutions’ for which the highest degree of membership functions can be reached. A real case example is considered to illustrate the proposed method, and findings show considerable scope for land re-allocation to achieve the aspired levels of production of different crops. Achieved land re-allocation with existing resource constraints the farm profits almost get doubled.